Teacher Strategies for Improving Reading Comprehension Skills through the Reflective Question-Based Think-Pair-Share Method in Indonesian Language Lessons at MTs Darul Furqon Kamal, West Kairatu, West Seram Regency, Maluku - Malihatus Saadah; Ulya Nurul Laili; Uswatun Hasanah; Harun Arrasyid; Andi Wapa (Cita konsultindo, 2026)
This study aimed to improve students' reading comprehension skills through the implementation of the Reflective Question-Based Think–Pair–Share (TPS) method in Indonesian language lessons at MTs Darul Furqon Kamal, West Kairatu, West Seram Regency, Maluku. The study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of two cycles, each including planning, action, observation, and reflection. The participants were 30 eighth-grade students and one Indonesian language teacher acting as a collaborative partner. Data were collected through classroom observations, reading comprehension tests, interviews, field notes, and documentation. Qualitative data were analyzed using data reduction, data display, and conclusion drawing, while quantitative data were analyzed by calculating the class mean and the percentage of students achieving the Minimum Mastery Criterion (KKM). The findings indicated that the implementation of the Think–Pair–Share method integrated with reflective questions successfully enhanced students' reading comprehension, classroom participation, and critical thinking skills. Students demonstrated significant improvement in identifying main ideas, making inferences, drawing conclusions, and responding to analytical questions throughout the two research cycles. Classroom interaction also became more active and collaborative as students engaged in individual thinking, peer discussion, and whole-class sharing. The study concludes that the Reflective Question-Based Think–Pair–Share method is an effective instructional strategy for improving reading comprehension and promoting active, student-centered learning in Indonesian language classrooms.